2017
DOI: 10.1002/ldr.2776
|View full text |Cite
|
Sign up to set email alerts
|

Afforestation, Subsequent Forest Fires and Provision of Hydrological Services: A Model‐Based Analysis for a Mediterranean Mountainous Catchment

Abstract: Mediterranean landscapes have experienced extensive abandonment and reforestation in recent decades, which should have improved the provision of hydrological services such as flood mitigation, soil erosion protection and water quality regulation. However, these forests are fire‐prone, and the postfire increase in runoff, erosion and sediment exports could negatively affect service provision. This issue was assessed by using the Soil and Water Assessment Tool model for the Macieira de Alcôba mountain catchment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 53 publications
(78 citation statements)
references
References 49 publications
3
75
0
Order By: Relevance
“…At the watershed level, the increase in the total annual streamflow in the wildfire scenario was considerably lower than the expected increase of 10–20% reported in several studies (Loáiciga, Pedreros, & Roberts, ; Neary, Ryan, & DeBano, ). That limited increase (0.3% total annual flow) is similar to the findings of Nunes, Naranjo Quintanilla, et al () when using the SWAT model to assess the streamflow in a small catchment partially affected by a wildfire. The results also agree with Hawtree et al's () assessment of afforestation in the Caramulo Mountains during the 20th century.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…At the watershed level, the increase in the total annual streamflow in the wildfire scenario was considerably lower than the expected increase of 10–20% reported in several studies (Loáiciga, Pedreros, & Roberts, ; Neary, Ryan, & DeBano, ). That limited increase (0.3% total annual flow) is similar to the findings of Nunes, Naranjo Quintanilla, et al () when using the SWAT model to assess the streamflow in a small catchment partially affected by a wildfire. The results also agree with Hawtree et al's () assessment of afforestation in the Caramulo Mountains during the 20th century.…”
Section: Discussionsupporting
confidence: 86%
“…Wildfires play a major role on land degradation in Mediterranean areas (Le Houérou, ). Notwithstanding, the number of wildfires is expected to increase due to climate change and new socioeconomic drivers (Nunes et al, ; Turco et al, ; Turco, Llasat, von Hardenberg, & Provenzale, ; Viedma, Moity, & Moreno, ). The reduction of vegetation and ground cover by wildfires increases soil susceptibility to raindrop impact.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Nyman, Sheridan, Smith, and Lane () showed that runoff‐generated debris flows dominated burned catchments in SE Australia; while in the Mediterranean, Shakesby () noted the absence of both mass failure and debris flows, implying the dominance of interill processes (Prats, Wagenbrenner, Santos Martins, Malvar, & Keizer, ). The dominant processes that govern contaminant mobilization are often controlled by higher‐order factors, for example, aridity controlling debris flows occurrence in Australia (Sheridan et al, ) or mobilization being affected by land use patterns (Nunes et al, ).…”
Section: A Framework For Predicting Post‐fire Water Contamination Risksmentioning
confidence: 99%
“…This exemplifies a situation where a large research focus on sediment mobilization (Tier 2 of the framework presented here) was not combined with a similar focus on transport (Tier 3 of the framework). This has recently been addressed by developing models which can account for the seasonal dynamics of hydrological connectivity in burnt areas (Nunes et al, , ; van Eck, Nunes, Vieira, Keesstra, & Keizer, ). These go some way in improving our ability to assess post‐fire contamination risk; a major uncertainty in adapting the Lisbon water supply to a changing environment (Groot, Rovisco, & Lourenço, ).…”
Section: The Framework In Practicementioning
confidence: 99%